Integrated spatial technology to mitigate greenhouse gas emissions in grain production - Engelbrecht, D.; Biswas, Wahidul; Pritchard, Deborah; Ahmad, W. (2015)
The causes and implications of climate change are currently at the forefront of many researching agendas. Countries that have ratified the Kyoto Protocol are bound by agreements to focus on and reduce greenhouse gas emissions which impact on the natural and anthropogenic environment. Internationally agriculture contributes to environmental impacts such as land use change, loss of biodiversity, greenhouse gas emissions, increased soil salinity, soil acidity and soil erosion. To combat and control the greenhouse gas emissions generated during agricultural production, methodologies are being developed and investigated worldwide. Agriculture is the second largest emitter of greenhouse gases in Australia and consequently the integrated spatial technology was developed using data from a crop rotation project conducted by the Department of Agriculture and Food, Western Australia. The aim of the integrated spatial technology was to combine remote sensing, geographical information systems and life cycle assessment, to ascertain the component or system within the agricultural production cycle, generating the most greenhouse gases. Cleaner production strategies were then used to develop mitigation measures for the reduction of greenhouse gases within the integrated spatial technology.